HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG VAKSINASI CORONA VIRUS DISEASE 2019 DENGAN KESEDIAAN MELAKUKAN VAKSINASI CORONA VIRUS DISEASE 2019 - Safitri, Diah; Dewi, Yulia Irvani; Amir, Yufitriana (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023, 2023)
Coronavirus Disease (Covid-19) is an infection that occurs in the respiratory tract due to the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS CoV-2) virus. Protective behavior with vaccination measures is an effort to protect against the spread of Covid-19 which can be done, especially in at-risk groups such as pregnant women. Lack of knowledge, the spread of negative opinions and the high feeling of worry about the impact of Covid-19 vaccination have resulted in a low level of willingness in pregnant women to be vaccinated compared to other populations. This study aims to determine the correlation between the level of knowledge of pregnant women regarding the Covid-19 vaccination and their willingness to carry out the vaccination. This research is included in the type of correlational quantitative research with a cross sectional design. The sample used in this study was 70 pregnant women who were selected using purposive sampling techniques. The sample inclusion criteria are pregnant women who have not been vaccinated against Covid-19 and the exclusion criteria are pregnant women with uncontrolled comorbidities and have a high risk (anemia, hyperemesis gravidarum, and preeclampsia). Data analysis using univariate and bivariate tests with chi-square statistical tests. The results of this study show that the majority of respondents have a high level of knowledge (51,4%) and some are willing to carry out the Covid-19 vaccination (75,7%). Based on the results of the chi-square test, it is known that there is a correlation between the level of knowledge of pregnant women regarding the Covid-19 vaccination and their willingness to be given the Covid-19 vaccine (p-value = 0.000). The conclusion obtained is that when the knowledge about administering the covid-19 vaccine to pregnant women is high, the willingness will also increase to carry out the vaccination.